1973
DOI: 10.1029/jb078i014p02526
|View full text |Cite
|
Sign up to set email alerts
|

Structure of East China Sea-West Philippine Sea Margin off southern Kyushu, Japan

Abstract: The results from seismic refraction profiles made south of Kyushu, Japan, are presented in a structure section crossing lhe outer East. China Sea shelf, the Okinawa trough, the Ryukyu ridge, the Ryukyu trench, the north Amami basin, the Kyushu-Palau ridge, and the western edge of the Shikoku basin. The foundation of the shelf-trough-ridge province is composed of material of velocity near 5.7 kin/sec. Above this material are others of velocity 3.4-4.6 km/sec that represent acoustic basement. The western edge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…In the northern part of the arc (outer arc), on the other hand, the velocity of the main crustal layer is 5.6 km s-', and is overlain by materials with velocities of 3.6 and 4.6 km sC1 (Ludwig et al 1973). …”
Section: The Ryukyu Island Arcmentioning
confidence: 99%
See 1 more Smart Citation
“…In the northern part of the arc (outer arc), on the other hand, the velocity of the main crustal layer is 5.6 km s-', and is overlain by materials with velocities of 3.6 and 4.6 km sC1 (Ludwig et al 1973). …”
Section: The Ryukyu Island Arcmentioning
confidence: 99%
“…However, most parts of the axial trough of the trench are not deeper than 6500 m. In the north, the trench is divided by the Amami plateau, which is west of the northern end of the Palau Ridge. The shape of the trench in this area is oval, with depths of approximately 5500 m. Ludwig et al (1973) showed that the crust beneath the northern part of the trench is oceanic but with a thinner than normal layer 3. Such a thin layer 3 was also found further south by Murauchi et af.…”
Section: The Ryukyu Trenchmentioning
confidence: 99%
“…However, previous seismic studies could not perfectly cover this study area without the distribution of event-station pairs crossing the East China Sea (Ludwing et al, 1973;Leyden et al, 1973;Hirata et al, 1991;Li et al, 2001). Because the event-station pairs are unique to Korean seismic stations, this study provides new information in this study area (Fig.…”
Section: Introductionmentioning
confidence: 85%
“…Previous studies in this area have used geophysical methods, such as magnetic, gravitational, sonobuoy seismic refraction, and ocean bottom seismometer (OBS) seismic refraction measurements (Ludwing et al, 1973;Leyden et al, 1973;Hirata et al, 1991;Li et al, 2001;Jiang et al, 2002;Lin et al, 2005;Fang and Liu, 2005;Han et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Dredge hauls and drill cores indicate the Daito Ridge to be a remnant island arc (e.g., KLEIN and KOBAYASHI, 1980). Seismic refraction profiling data over the Oki Daito Ridge and the Kyushu Palau Ridge show thick crust with velocities similar to those of continents (MURAUCHI et al, 1968;LUDWIG et al, 1973). It is not known whether these anomalous regions are seismically active or not except the Central Basin Fault.…”
mentioning
confidence: 99%